Implikasi yurіdіs penandatanganan akta dі hadapan notarіs dengan menggunakan tanda tangan elektronіk - Nuke Irfayanti Lubis (Jurnal Cakrawala Hukum, 2021)
Indonesia is in an era of globalization, it can be seen by the era of technology that introduced the virtual world (cyberspace, virtual world) through internet networks, communication with electronic media without paper. The development of electronic signature technology has been implemented in Indonesia. The existence of electronic signatures has begun to replace conventional signatures in several places on the grounds of using technology to make it easier. The ІTE Act already guarantees electronic signatures. GMS can be held using electoral media. However, the GMS with electronic media must be approved and signed by the GMS participants. In the notary deed, the minutes of the GMS are included in the release deed. Preparation of a notary deed of the GMS minutes using an electronic system must be signed by all GMS participants. Participants who attend the meeting via video conference can use the signature using the electronic system. Legal Issues in this Research There are unclear norms related to signatures which are described in the Law on Notary Position. This research is normative law research. From the results of the research using the above method, the author obtains answers to the problems regarding the Law of Signing Notary Deeds Using Electronic Signatures.How to cite item: Lubis, N., (2021). Implikasi yurіdіs penandatanganan akta dі hadapan notarіs dengan menggunakan tanda tangan elektronіk. Jurnal Cakrawala Hukum, 12(3), 314-325. doi:https://doi.org/10.26905/idjch.v12i3.5114.